Barriers to Lead Psychiatric Clinical Supervision – A Cross-Sectional Survey - Zaib un Nisa; Zong Lai; Kehinde Junaid; Bala Ganesan; Sudheer Lankappa (BJPsych Open)
Aims: The Royal College of Psychiatrists (RCPsych) recommends that psychiatric trainees receive one hour of 1:1 supervision per week, with clinical supervisors allocated 0.25 PA (programmed activity) protected time per trainee weekly. The GMC National Training Survey 2023 found that 86% of trainees reported positive feedback on clinical supervision, though the survey was not psychiatry specific. Locally, the Resident Doctors Forum raised concerns about some trainees not receiving the recommended supervision time, prompting the introduction of a new supervision form.